Programa para alimentação saudável: efeito sobre antropometria e hábitos alimentares em escolares - Santini, Andréia de Pelegrini (2013)
The school space emerges as a conducive environment for the implementation of health education programs that promote healthy eating habits since they can influence both in children and in their families. Thus, this study aimed to evaluate the effects of a nutrition education program on growth, nutritional status, eating habits and knowledge of food and hygiene in school 2nd and 3rd year of municipal schools in the city of Santa Maria/RS. Intervention study of 83 schoolchildren between 6 and 10 years of age, 50.6% girls in a municipal school in Santa Maria, from March to July 2012. It was performed anthropometry and administered a questionnaire on dietary habits and knowledge of healthy eating and hygiene, before and after eight meetings, addressing: Origin of Food, Stimulate Production of kitchen garden ( Horta ), Hygiene and Food Handling, Encouraging consumption of fruits and vegetables, Going to the Supermarket and Food, Production Workshop. For statistical analysis we used frequency distribution, mean, median (after evaluation of the normality of the variables using the Shapiro Wilk test), Student's t test, Fisher's exact and Wilcoxon, considering a significance level of p <0.05. The median weight, height, BMI, waist circumference and weight Z-score was higher in the post-intervention. Were eutrophic and overweight, respectively, 72.3% and 25.3% of students, rising to 65.1% and 33.7%, at reassessment (p<0.001). There was an increase of the habit of eating breakfast (from 69.9 to 71.1%), eating bread (from 59.0 to 69.9%), dairy products (71.1 to 77.1%) and vegetables (53.0 to 59.0%), and there was a reduction in exchanging lunch and dinner with a snack, meals while watching television (63.9% to 47.0%), soft drink consumption (62, 6% to 38.5%), artificial juice (from 51.8% to 34.9%) and sweets intake (from 55.4% to 36.1%). The mean total score on the questionnaire about dietary habits fell from 32.1 to 33.2 points (p<0.05). In both evaluations no schoolchildren was rated as having poor eating habits and an increase in the percentage of children with great eating habits (18.1% to 36.1%). There was an improvement in the hits about food and hygiene knowledge, but with significant difference only in knowledge about the origin of food (from 73.5% to 91.6%). It is concluded that the tendency to excess body weight remained in school, while education for healthy eating has resulted in improvement in knowledge and eating habits which emphasizes the importance of these programs in schools elementary level.